2022
DOI: 10.1123/ijsnem.2021-0330
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-Rich Blackcurrant Extract Preserves Gastrointestinal Barrier Permeability and Reduces Enterocyte Damage but Has No Effect on Microbial Translocation and Inflammation After Exertional Heat Stress

Abstract: This study investigated the effects of 7 days of 600 mg/day anthocyanin-rich blackcurrant extract intake on small intestinal permeability, enterocyte damage, microbial translocation, and inflammation following exertional heat stress. Twelve recreationally active men (maximal aerobic capacity = 55.6 ± 6.0 ml·kg−1·min−1) ran (70% VO2max) for 60 min in an environmental chamber (34 °C, 40% relative humidity) on two occasions (placebo/blackcurrant, randomized double-blind crossover). Permeability was assessed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In clinical situation, changes in the types of diet can be easy for some people patients but hard for others. The development of supplements that contain various phytochemicals with anti-inflammatory effects 77,80,85 or milk glycan that improves gut microbiota profile 74 may help reducing the symptoms and/or can ameliorate the impacts of high-fat diet. Many studies have been done on the potential pharmaceutical treatments for GWI.…”
Section: High-fat Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical situation, changes in the types of diet can be easy for some people patients but hard for others. The development of supplements that contain various phytochemicals with anti-inflammatory effects 77,80,85 or milk glycan that improves gut microbiota profile 74 may help reducing the symptoms and/or can ameliorate the impacts of high-fat diet. Many studies have been done on the potential pharmaceutical treatments for GWI.…”
Section: High-fat Dietmentioning
confidence: 99%
“…Studies using animal models showing the causation of the symptoms of GWI are also accumulating (Figure 2, Table 2). The new studies showing promising results to improve the GWI symptoms can be the new directions in treating GWI: the intestine EVs, 57 utilization of the phytochemicals with anti-inflammatory effects 77,80,85,91 and reducing the intake of highfat diet. 90 All of these have shown positive results in animal model studies as shown above.…”
Section: High-fat Dietmentioning
confidence: 99%
“…May ↓ intestinal permeability and microbial translocation, but findings are inconsistent (Ashton et al., 2003 ; Kuennen et al., 2011 ; Lee et al., 2022 ; Szymanski et al., 2018 )…”
Section: Nutrition and Ehs Riskmentioning
confidence: 99%
“…For example, 3 weeks of quercetin (1 g day −1 ) had no influence on plasma cytokine responses to 3 h of moderate‐intensity cycling, but a single 2 g dose blunted intestinal permeability, microbial translocation and plasma TNF‐α following 40 min of exertional‐heat stress (Kuennen et al., 2011 ; Nieman et al., 2007 ). One recent human study reported that 7 days’ supplementation with anthocyanin‐rich blackcurrant extract, another flavonoid antioxidant, protected intestinal permeability in response to exertional‐heat stress; however, these benefits did not extend to blunted microbial translocation or systemic inflammation (Lee et al., 2022 ).…”
Section: Nutrition and Ehs Riskmentioning
confidence: 99%
See 1 more Smart Citation